The Level Of Positive Thinking And Its Relationship To Feelings Of Loss Among Mothers Of Deceased Children In Jordan - Al- Momani, Amani Ali Ahmad; Banat, Suhaila Mahmud (Journal of Educational and Psychological Sciences, 2019)
The study aimed at identifying the level of positive thinking practice and its relation to feelings of loss among mothers whose children died in Jordan. The study sample consisted of (125) mother who lost one or more sons from the northern governorates (Irbid, Ajloun and Jerash). To achieve the objectives of the study, the researcher developed the measures of the study which are: the measure of positive thinking, consisting of (51) paragraph, and the measure of feelings of loss, consisting of (59) paragraph. The results showed that the level of feelings of loss among mothers whose children died was moderate. The results showed that the level of positive thinking of mothers whose sons died was high; the results showed that there was no correlation between positive thinking and feelings of loss. The results of the study showed that there were no differences due to the variable age in the level of positive thinking, while there were differences due to scientific qualifications in favor of mothers who have Bachelor's degree and above. Regarding the feelings of loss, no differences were found due to the age variables and the scientific qualification of mothers whose sons died.In light of these findings, the researcher recommends more qualitative and experimental studies on mothers whose children died.
Keywords: positive thinking; feelings of loss; mothers; Jordan